Leveraging the role of MSMEs for healthier diets and nutrition: Insights from fruit and vegetable value chain studies across five countries - Nguyen, Trang; Termeer, Emma; Berkhout, Ezra; Mekonnen, Daniel Ayalew; Dijkxhoorn, Youri; de Steenhuijsen Pieters, Bart (International Food Policy Research Institute, 2024)
In most low and middle-income countries (LMICs) the food system falls short in providing sufficient amounts of healthy foods to a burgeoning population. The growing awareness of how food systems are stressing planetary boundaries and failing to provide sustainable healthy diets and livelihoods has prompted the widespread call to transform the global food system (Béné 2022; FAO et al. 2020, 2024; Webb et al. 2020). Transforming food systems requires engaging various groups of actors with diverse perspectives and challenges (Leeuwis et al. 2021), including setting up alliances with the informal sector (Brouwer & Ruben 2021) and a strengthened focus on the role of micro-, small- and medium-sized enterprises (MSMEs).